Analisis Kasus Pencurian Menurut Pasal 362 KUHP Dan Hadist Bukhari No. 6285 - Dalva Aulia Apandi; Tajul Arifin (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This research aims to analyze cases of theft based on Article 362 of the Criminal Code and Hadith Bukhari no. 6285. The research method used is qualitative with case studies. Data was collected through literature studies and analysis of court decisions related to theft cases. The research results show that Article 362 of the Criminal Code and Hadith Bukhari no. 6285 has similarities and differences in defining and regulating the crime of theft. The similarities lie in the elements of theft, namely taking something that does not belong to you with the intention of possessing it. The difference lies in the sanctions given, where the Criminal Code provides for imprisonment, while Hadith Bukhari no. 6285 sanctions caning. It can be concluded from this research that Article 362 of the Criminal Code and Hadith Bukhari no. 6285 are two different sources of law in regulating the crime of theft. Even though they have similarities and differences, these two sources of law have the same goal, namely to protect property rights and uphold justice.